Taṭbīq aṭ-Ṭarīqah al-Mubāsyarah Bi Biṭṭāqah Kwartet Li Tarqiyah Qudrah aṭ-Ṭullāb `Alā at-Ta`bīr asy-Syafawī (Dirāsah Tajrībiyah Bi al-Madrasah al-`Aliyah al-Islāmiyyah Rūḥ al-Falāḥ Samahani) - Nurdina Afrah; Moch. Fajarul Falah; Nur Chalis (The Department of Arabic Language Education, Pascasarjana Universitas Islam Negeri Banda Aceh of UIN Ar-Raniry Banda Aceh, Aceh, Indonesia., 2020)
The subject of the study was